# How could we rewrite this integral as the other one i provided and how to solve it? [duplicate]

Possible Duplicate:
Value of $\sum x^n$

How do you rewrite this: $$\int_{0}^{\infty} \cfrac{1}{1+x^4}$$

to: this$$\int_{0}^1 \sum_{n=0}^\infty (-1)^n x^{4n} + \int_{1}^\infty x^{-4} \sum_{n=0}^{\infty} (-1)^n x^{-4n}$$

and how do you solve it?

-

## marked as duplicate by t.b., Did, Srivatsan, Sasha, Asaf KaragilaJan 1 '12 at 19:41

Do you know the closed formula for $\sum_k^n x^k$? What happens if $n$ tends to inifinity? And what would be the formula for $\sum x^{-k}$? – user20266 Jan 1 '12 at 17:46
@Victor It is not totally different. Hint: substitute $x=-t^4$ to the formula behind t.b.'s link. Your textbook probably explains, when it is permissible to integrate a series term-by-term (that is not automatic!). – Jyrki Lahtonen Jan 1 '12 at 18:30
To rewrite it, you need to know the geometric series expansion, $$\frac{1}{1+z} = 1-z+z^2-z^3+...=\sum_{n=0}^{\infty} (-1)^{n}z^{n},$$ and know that it converges absolutely for all $|z|<1$. There are two different geometric series expansions for $(1+x^4)^{-1}$; one is the Taylor series expansion, good for small $x$, and the other is the Laurent series expansion, good for large $x$. They are $$\frac{1}{1+x^4} = 1-x^4+x^8-...=\sum_{n=0}^{\infty}(-1)^{n}x^{4n}$$ and $$\frac{1}{1+x^4}=\frac{1}{x^4}\frac{1}{1+x^{-4}}=\frac{1}{x^4}\left(1-x^{-4}+x^{-8}-...\right)=\sum_{n=0}^{\infty}(-1)^n x^{-4-4n}.$$ These series converge absolutely when $|x^4|<1$ and when $|x^{-4}|<1$ respectively (i.e., for $|x|<1$ and for $|x|>1$). So we have $$\begin{eqnarray} I=\int_{0}^{\infty}\frac{dx}{1+x^4}&=&\int_{0}^{1}\frac{dx}{1+x^4}+\int_{1}^{\infty}\frac{dx}{1+x^4} \\ &=&\int_{0}^{1}dx\sum_{n=0}^{\infty}(-1)^n x^{4n}+\int_{1}^{\infty}dx\sum_{n=0}^{\infty}(-1)^{n}x^{-4-4n}\\ &=&\sum_{n=0}^{\infty}(-1)^{n}\left(\int_{0}^{1}x^{4n}dx + \int_{1}^{\infty}x^{-4-4n}dx\right), \end{eqnarray}$$ where we need the absolute convergence of the sums to justify exchanging the sums and the integrals. The integrals are elementary: $$\int_{0}^{1}x^{4n}dx = \frac{x^{4n+1}}{4n+1}\Bigg\vert_{0}^{1} = \frac{1}{4n+1}$$ and $$\int_{1}^{\infty}x^{-4-4n}dx = \frac{x^{-3-4n}}{-3-4n}\Bigg\vert_{1}^{\infty} = \frac{1}{4n+3},$$ giving the result $$\begin{eqnarray} I &=& \sum_{n=0}^{\infty}(-1)^{n}\left(\frac{1}{4n+1} + \frac{1}{4n+3}\right) \\ &=& \sum_{n=0}^{\infty} \frac{\sigma_{n}}{2n+1} \\ &=& 1 + \frac{1}{3} - \frac{1}{5} - \frac{1}{7} + \frac{1}{9} + \frac{1}{13} - \text{...}, \end{eqnarray}$$ where $\sigma=\{1,1,-1,-1,1,1,-1,-1,...\}$.